MEJA LUKIS WAYANG DENGAN MEDIA KACA UNTUK MENINGKATKAN KINERJA PELUKIS WAYANG DI SMP NEGERI NO 3 PADANG BULIA, SINGARAJA - Koriawan, Gede Eka Harsana (Universitas Pendidikan Ganesha, 2017)
The students of SMPN 3 Padang Bulia who joined extracurricular activity of painting with glass medium mostly had issues on back pain, waist pain, and neck pain. This was caused by innatural working attitude resulted from the working table which is not ergonomic. The research was to find out the effect of working table on muscolo celetal and the improvement of students’ working quality. In this qualitative research, the data were collected by observation technique, interview and anthropometry measurement of the painters. The data analyzed were the students’ body attitude when they are working on table with the anthropometry’s measurement in order that it is possible to make suitable working table to improve their productivity. From this research, the size of ergonomic working table for students’ anthropometry when they are painting was found. Table was made sideways with 15-45 degree and the height of the painters’ elbow position is 5-8 cm under the table’s surface attempted to be equal with the table’s height. The working table’s design which is ergonomic can decrease the pain of musculo celetal and can improve the painter’s productivity